A review of land settlements in the Philippines 1900-1975 - Paderanga, Cayetano W., Jr. (1987)
The history of land settlement programs in the Philippines from 1900 to 1975 is reviewed from secondary sources, including three case studies. A few similarities are noticed among all of the resettlement movements.
Keywords: Land settlement; Economic policy